Association of enzyme and transporter genotypes with the pharmacokinetics of imatinib - Gardner, Erin R; Burger, Herman; van Schaik, Ron H; van Oosterom, Allan T; de Bruijn, Ernst A; Guetens, Gunther; Prenen, Hans; de Jong, Floris A; Baker, Sharyn D; Bates, Susan E; Figg, William D; Verweij, Jaap; et al. (Clinical pharmacology and therapeutics, 2006)
Our objective was to explore the relationships between imatinib pharmacokinetics and 9 allelic variants in 7 genes coding for adenosine triphosphate-binding cassette transporters (ABCB1 and ABCG2) and enzymes (cytochrome P450 [CYP] 2C9, CYP2C19, CYP2D6, CYP3A4, and CYP3A5) of putative relevance for imatinib. Imatinib transport in vitro was studied by use of human embryonic kidney 293 cells transfected with wild-type ABCG2 and an ABCG2 Q141K clone. Steady-state pharmacokinetics of imatinib was obtained in 82 patients with gastrointestinal stromal tumors treated with oral imatinib at doses ranging from 100 to 1000 mg/d. Genotyping was carried out via direct sequencing or restriction fragment length polymorphism-based techniques. Human embryonic kidney 293 cells transfected with ABCG2 Q141K exhibited greater drug accumulation in vitro in comparison with cells expressing wild-type ABCG2 (P = .028). However, pharmacokinetic parameters of imatinib in vivo were not statistically significantly different in 16 patients who were heterozygous for ABCG2 421C>A compared with 66 patients carrying the wild-type sequence (P = .479). The apparent oral clearance of imatinib was potentially reduced in individuals with at least 1 CYP2D6*4 allele (median, 7.78 versus 10.6 L/h; P = .0695). Pharmacokinetic parameters were not related to any of the other multiple-variant genotypes (P >or= .230), possibly because of the low allele frequencies. This study indicates that common genetic variants in the evaluated genes have only a limited impact on the pharmacokinetics of imatinib. Further investigation is required to quantitatively assess the clinical significance of homozygous variant ABCG2 and CYP2D6 genotypes in patients treated with imatinib.